THE EFFECTIVENESS OF MIND MAPPING TECHNIQUE WITH COGNITIVE APPROACH IN CLASSICAL GUIDANCE TO IMPROVE THE CAREER MATURITY OF STUDENTS OF CLASS X SMKS TARUNA MANDIRI SRONO: EFEKTIVITAS TEKNIK MIND MAPPING DENGAN PENDEKATAN KOGNITIF DALAM BIMBINGAN KLASIKAL UNTUK MENINGKATKAN KEMATANGAN KARIR SISWA KELAS X SMKS TARUNA MANDIRI SRONO - Veronica, Shintya; Wicaksono, Heriberthus; Wahyu Prasetyo, Fajar (BIMBINGAN DAN KONSELING BANYUWANGI, 2024)
This research was conducted to determine the effectiveness of mind mapping technique with cognitive approach in classical guidance to improve the career maturity of students of class X SMKS Taruna Mandiri Srono. This research used quasi-experiment with non-equivalent control group deisgn, the two groups, both pre-test and post-test.The sample of this research used saturated sampling technique. The sample amounted to 29 students out of 29 total. The data collection techniques used were observation career maturity questionnaires, and interviews. Researchers used data analysis techniques with statictical program for social sciences (SPSS) 25 for windows. the results showed that mind mapping techniques with cognitive approaches in classical guidance proved effective for increasing the career maturity of class X students of SMKS Taruna Mandiri Srono.